Wealth Management sebagai Strategi Pengelolaan Aset di PPPA Daarul Qur’an Yogyakarta - Deni Titin Ragil Wulandari; Imam Machali (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
This research was conducted to study the management of assets in Islamic educational institutions. Financial assets and human resources management are the key component needs to be managed professionally in order to produce qualified educational output in PPPA Daarul Qur'an, Yogyakarta branch. This is a descriptive qualitative research in which data were collected through interviews, documentation and observations. The results showed that: 1) wealth management of PPPA Daarul Qur'an Yogyakarta branch is carried out using the systemic-communicative concept. 2) analysed by Robert T. Kiyosaki quadrant, Non-human asset management in the form of fund management can be categorised as Sd (Student Donation) which comes from donors; Business that comes from the businesses owned by Daarul Qur'an; and Gd (Government and private donation) derived from the Corporate Social Responsibility (CSR) Program of several companies. The management was conducted through the principle of transparency, public accountability, efficiency and effectiveness. While human resource management refers to operational functions in the form of procurement, development, integration, maintenance, and separation. The implementation of wealth management can improve the quality of asset management in Islamic educational institutions.